ANALISIS KETAHANAN PANGAN SERTA KESEJAHTERAAN RUMAH TANGGA PETANI KOPI UNTUK PEMBANGUNAN DAERAH BERKELANJUTAN DI PROVINSI SUMATERA UTARA - M. Fariz Afif Hasibuan; Hendris Syah Putra; Chairia Chairia; Heni Naura Putri Hendro; Icha Aprilia (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2025)
The purpose of this study is to evaluate the level of food security and household welfare of coffee farmers in Samosir Regency, North Sumatra Province, within the context of sustainable regional development. The research involved thirty purposively selected coffee farmers through household surveys, interviews, and focus group discussions (FGDs). To determine the components influencing food security in households, the analysis employed an ordinal logistic regression model. The results revealed that 46.7% of households were classified as food secure, with the average energy adequacy rate among coffee farmers reaching 82.9% of the Recommended Dietary Allowance (RDA) established by WKNPG 2012. The level of food security was significantly affected by household income and the education level of the housewife at confidence levels of 95% and 90%, respectively. Conversely, household size, food prices, and food access had no significant effect. According to this study, improving food security and the welfare of farmers within the framework of sustainable regional development must be accompanied by enhanced educational capacity and household nutritional literacy, as well as income diversification to strengthen the resilience and welfare of coffee-farming households.